The Charter: a plea for tolerance - Hamans, Camiel (Scripta Neophilologica Posnaniensia, 2019)
This paper describes the background of the Charter for Regional and Minority Languages (1992). To explain why linguistic diversity became an issue in the last decades of the 20th century, the paper goes back to the end of the 18th and the 19th century, a period in which nation building and homogenization were the main political issues in Western Europe. Since language was seen as nation binder language diversity was anathema. This led to language conflicts, which were sought to be solved by means of the Charter that promoted the acceptance of language diversity.